Hindering the Oxidation of Silicene with Non‐Reactive Encapsulation. (9th April 2013) - Molle, Alessandro; Grazianetti, Carlo; Chiappe, Daniele; Cinquanta, Eugenio; Cianci, Elena; Tallarida, Grazia; Fanciulli, Marco
Abstract The chemical stability of buckled silicene, i.e., the silicon counterpart of graphene, is investigated then resulting in a low reactivity with O2 when dosing up to 1000 L and in a progressive oxidation under ambient conditions. The latter drawback is addressed by engineering ad hoc Al‐ and Al2O3‐based encapsulations of the silicene layer. This encapsulation design can be generally applied to any silicene configuration, irrespective of the support substrate, and it leads to the fabrication of atomically sharp and chemically intact Al/silicene and Al2O3/silicene interfaces that can be functionally used for ex situ characterization as well as for gated device fabrication.